Climate Change and Agrometeorology - Ahmad, Latief; Biswas, Asim.; Warland, Jon.; Anjum, Insha (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
The monograph focuses on agricultural meteorology and climate change and its impacts on different crops. Comprising of chapters from experts, the book discusses and provides first-hand information to the long term shifts in weather patterns and temperature impacting soil, water and crops. Each chapter focuses in detail on the impact of plant- water - soil nexus and climate change on agriculture and food security. Covering the basic concepts about the temperature, pressure and humidity correlation with the increased demands of food, the book explores in detail the impact of adverse climatic conditions like drought, floods, increasing levels of carbon dioxide emissions and other simultaneous effects like soil fertility depletion on the cropping systems and overall crop productivity. The book touches the challenges of climate change, adaptive methods, mitigation strategies, with careful explanation of governance, plans and policies required to provide guidelines to stake holders so they can best prepare for the negative climate change impacts. While touching the agricultural challenges faced globally due to climate change, the book serves as a reference book for students, researchers and policy makers, involved in horticulture, agriculture and environmental sciences and climate change.
Preface -- About the Authors -- Chapter 1 Agricultural Meteorology: A Preview -- Chapter 2 Atmospheric Temperature -- Chapter 3 Atmospheric Pressure and Solar Radiation -- Chapter 4 Atmospheric Humidity -- Chapter 5 Microclimate and Climatic Normals -- Chapter 6 Weather Disasters and Management, Air Pollution and Role of Meteorology -- Chapter 7 Weather Forecasting -- Chapter 8 Climate Change Impact on Plants -- Chapter 9 Climate Change Effect on Fruit Production -- Chapter 10 Climate change Effect on Forests.
Keywords: Agriculture; Bioclimatology; Climatology; Human ecology -- Study and teaching; Agriculture; Climate Change Ecology; Climate Sciences; Environmental Studies